Экспрессия онкобелка Е6 вируса папилломы человека в эпителии придатков матки при раке яичника и генетической предрасположенности к нему - Билык, Е.А.; Бучинская, Л.Г.; Полищук, Л.З.; Проскурня, Л.А.; Пеёвич, Т. (Онкологія, 2011)
Проведено комплексное морфологическое и иммуногистохимиче-
ское исследование придатков матки у 20 женщин с генетической предрас-
положенностью к развитию рака яичников (РЯ) и 55 больных РЯ. У 60,0%
женщин с высоким риском РЯ выявлена экспрессия онкобелка Е6 вируса па-
пилломы человека (ВПЧ)16 и18 типов в эпителии маточных труб, поверх-
ностном эпителии яичников, гранулезных клетках фолликулов, эпителии
фолликулярных кист и эндотелии сосудов. У 16,3% больных РЯ установлено
наличие вирусного онкобелка в опухолевых клетках. Экспрессия опухолево-
го супрессора р53 отсутствовала в ткани инфицированных ВПЧ яичников
женщин с высоким риском РЯ и была достоверно ниже в ВПЧ-позитивном
РЯ по сравнению с ВПЧ-негативными опухолями. Предполагается, что па-
пилломавирусная инфекция может являться дополнительным экзогенным
фактором злокачественной трансформации эпителия яичников. Ключевые слова: рак яичника,
онкобелок Е6, вирус папилломы
человека, р53, генетическая
предрасположенность к раку. Complex morphological and immunohisto
chemical study of adnexa uteri in 20 women with
genetic predisposition to ovarian cancer (OC) and 55
OC patients was carried out. The presence of HPV
16/18 E6 oncoprotein in epithelial lining of fallopian
tubes, ovarian surface epithelium, granulose cells of
follicules, epithelium of follicular cysts and endothelial
cells was revealed in 60% of women at high risk of
developing OC. Tumor cells of 16,3% of OC patients
were also positive for HPV 16/18 E6 oncoprotein.
Expression of tumor suppressor protein p53 was absent
in HPV-positive ovarian tissues in women at high risk
of developing ovarian cancer and was significantly
lower in HPV-positive OC compared to HPV-negative
tumors. It is assumed that papillomavirus infection
can be an addition exogenous inductor of malignant
transformation of ovarian epithelium. Complex morphological and immunohisto
chemical study of adnexa uteri in 20 women with
genetic predisposition to ovarian cancer (OC) and 55
OC patients was carried out. The presence of HPV
16/18 E6 oncoprotein in epithelial lining of fallopian
tubes, ovarian surface epithelium, granulose cells of
follicules, epithelium of follicular cysts and endothelial
cells was revealed in 60% of women at high risk of
developing OC. Tumor cells of 16,3% of OC patients
were also positive for HPV 16/18 E6 oncoprotein.
Expression of tumor suppressor protein p53 was absent
in HPV-positive ovarian tissues in women at high risk
of developing ovarian cancer and was significantly
lower in HPV-positive OC compared to HPV-negative
tumors. It is assumed that papillomavirus infection
can be an addition exogenous inductor of malignant
transformation of ovarian epithelium.Complex morphological and immunohisto
chemical study of adnexa uteri in 20 women with
genetic predisposition to ovarian cancer (OC) and 55
OC patients was carried out. The presence of HPV
16/18 E6 oncoprotein in epithelial lining of fallopian
tubes, ovarian surface epithelium, granulose cells of
follicules, epithelium of follicular cysts and endothelial
cells was revealed in 60% of women at high risk of
developing OC. Tumor cells of 16,3% of OC patients
were also positive for HPV 16/18 E6 oncoprotein.
Expression of tumor suppressor protein p53 was absent
in HPV-positive ovarian tissues in women at high risk
of developing ovarian cancer and was significantly
lower in HPV-positive OC compared to HPV-negative
tumors. It is assumed that papillomavirus infection
can be an addition exogenous inductor of malignant
transformation of ovarian epithelium.Complex morphological and immunohisto
chemical study of adnexa uteri in 20 women with
genetic predisposition to ovarian cancer (OC) and 55
OC patients was carried out. The presence of HPV
16/18 E6 oncoprotein in epithelial lining of fallopian
tubes, ovarian surface epithelium, granulose cells of
follicules, epithelium of follicular cysts and endothelial
cells was revealed in 60% of women at high risk of
developing OC. Tumor cells of 16,3% of OC patients
were also positive for HPV 16/18 E6 oncoprotein.
Expression of tumor suppressor protein p53 was absent
in HPV-positive ovarian tissues in women at high risk
of developing ovarian cancer and was significantly
lower in HPV-positive OC compared to HPV-negative
tumors. It is assumed that papillomavirus infection
can be an addition exogenous inductor of malignant
transformation of ovarian epithelium. Key Words: ovarian cancer, oncoprotein Е6,
human papillomavirus, р53, genetic susceptibility
to cancer.